Clinical features of febrile seizures in children with COVID-19: an observational study from a tertiary care hospital in China - Fang, Cuiyun; Zhou, Yuan; Fan, Wei; Zhang, Chunsheng; Yang, Yi (Frontiers in Pediatrics, 2023)
Background: Febrile seizures are a common neurologic manifestation in children with coronavirus disease 2019 . Compared to seasonal respiratory viruses, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has a pronounced neurological impact, with the result that febrile seizures with COVID-19 may exhibit unique clinical features.We conducted a retrospective study in a tertiary care hospital in China. We collected medical record information on febrile seizures with COVID-19, including demographic characteristics, clinical features, laboratory tests, and disease burden. Subsequently, the data were then analyzed descriptively. Results: A total of 103 children diagnosed with febrile seizures and positive COVID-19 PCR results were included in our study. Among them, 81 (78.6%) were males and 22 (21.4%) were females. The age of onset of febrile seizures ranged from 14 to 57 months, with a mean age of 34.9±6.24 months. Complex febrile seizures were observed in 34 (33%) cases. Antiseizure medications were administered to 24 (23.3%) patients. Laboratory tests showed a white blood cell count of (27.05 ± 8.20) × 10 3 /µL, a neutrophil count of (20.09 ± 5.66) × 10 3 /µL and a lymphocyte count of (6.44± 1.86) ×10 3 /µL. A creatine kinase level was significantly elevated, with a mean value of (412.00 ± 158.96) U/L. The mean length of stay was 4.36 days. Twelve patients (11.7%) required intensive care services, but there were no deaths or patients remaining on antiseizure medications after discharge.In the post-epidemic era of COVID-19, pediatric clinicians should be aware of the changing clinical features of febrile seizures associated with COVID-19. The average age of onset has increased, with a higher proportion of males. Length of stay and hospitalization costs did not increase significantly. The prognosis remained favorable, although a small number of children required intensive care services during the acute phase.